2018
DOI: 10.1016/j.ebiom.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific effects of targeted mutation of Mir29b1 in rats

Abstract: Background miR-29 is a master regulator of extracellular matrix genes, but conflicting data on its anti-fibrotic effect have been reported. miR-29 improves nitric oxide (NO) production in arterioles by targeting Lypla1. Mir29b1 targeted mutation exacerbates hypertension in a model derived from the Dahl salt-sensitive rat. We examined the effect of Mir29b1 mutation on tissue fibrosis and NO levels with a focus on kidney regions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(62 reference statements)
3
7
0
Order By: Relevance
“…miRNA-29 is highly expressed in glioma tumorigenesis (30), pancreatic ductal adenocarcinoma (31) and chronic liver damage (32). It is noteworthy that miRNA-29 has been reported to be involved in the regulation of intestinal permeability and epithelial barrier function (33,34). Consistent with early research (35), the present results demonstrated that miRNA-29a was significantly increased in patients with IBS-D compared with the control, indicating that miRNA-29a serves a role in IBS-D.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…miRNA-29 is highly expressed in glioma tumorigenesis (30), pancreatic ductal adenocarcinoma (31) and chronic liver damage (32). It is noteworthy that miRNA-29 has been reported to be involved in the regulation of intestinal permeability and epithelial barrier function (33,34). Consistent with early research (35), the present results demonstrated that miRNA-29a was significantly increased in patients with IBS-D compared with the control, indicating that miRNA-29a serves a role in IBS-D.…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, since at least two investigators evaluated and agreed to the clinical symptoms, the study was single blinded. Thirdly, a previous study showed that CLDN-1 is the direct target of miRNA-29a (34). We were unable to conclusively determine whether ZO-1 is a direct target of miRNA-29a.…”
Section: Discussionmentioning
confidence: 73%
“…PLA2G4 is one of the mammalian PLA2 enzymes hydrolyzing phospholipids to release arachidonic acid, which is a precursor for prostaglandins. As a key factor, PLA2G4 contributes to the development of hypertension and renal injury in various animal models [29,30,47,48]. In the present work, we found that the E. faecalis induced expression of Lypla1 and Pla2g4 was later than other lipid metabolic genes, such as Aspg, Plb1 and Gde1, and only in the renal medulla (Fig.…”
Section: Enterococcus Faecalis Contributes To Hypertension and Renal ...supporting
confidence: 56%
“…Especially, the expression of LYPLA1 but not LYPLA2 was markedly elevated in the renal medulla of E. faecalis -induced hypertensive rats. Similar expression pattern of LYPLA1 was also reported in the renal medulla of high-salt fed Dahl salt-sensitive rats ( Xue et al., 2018 ), suggesting it may be involved in sodium homeostasis. Hence, we hypothesized that renal LYPLA1 may contribute to the pathogenesis of E. faecalis -induced hypertension by regulating sodium homeostasis.…”
Section: Introductionsupporting
confidence: 81%
“…As a lipid-metabolizing enzyme, the increased expression of LYPLA1 in the renal medulla has been reported in high salt-fed Dahl salt-sensitive rats( Xue et al., 2018 ) and E. faecalis -induced hypertensive rats( Zhu et al., 2021 ), but the role of LYPLA1 in the kidney is poorly defined. In this work, we found that the lypla1 knockdown in the kidney dramatically blocked E. faecalis -induced hypertension and sodium reabsorption ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%